2008
DOI: 10.1002/jnr.21625
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived cells expressing Iba1 are constitutively present as resident tissue macrophages in the mouse cochlea

Abstract: Immune-mediated inner ear disorder has been well established as a clinical entity; however, the innate immune system of the inner ear is a poorly understood area of research with high clinical and immunological importance. Although the presence of resident tissue macrophages in the inner ear has been suggested, there has been some controversy. In this study, we analyzed the origin of cochlear resident macrophages and the contribution of hematopoietic bone marrow (BM) to the recruitment of macrophages in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
190
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(202 citation statements)
references
References 29 publications
10
190
1
1
Order By: Relevance
“…TNF-> is known to cause accumulation of proinflammatory cells in the cochlea (8). Suppression of infiltration of these cells with inhibition of TNF-> signal was shown to reduce hearing loss in animal models (9).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-> is known to cause accumulation of proinflammatory cells in the cochlea (8). Suppression of infiltration of these cells with inhibition of TNF-> signal was shown to reduce hearing loss in animal models (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies indicate importance of the spiral ligament in the immune reaction in the cochlea. Macrophages and/or microglia are constitutively present in the spiral ligament and accumulate in response to injury (Hirose et al, 2005;Okano et al, 2008;Sato et al, 2008). The spiral ligament fibrocytes produce cytokines in response to exposure to bacterial toxins (Moon et al, 2006(Moon et al, , 2007 and noise exposure (Fujioka et al, 2006).…”
Section: Possible Role Of Ep Signaling In the Cochlear Sensory Systemmentioning
confidence: 99%
“…One of the mechanisms of secondary damage might be a local increase in the inflammatory response and proinflammatory cytokines because these cytokines rise endogenously in the first 2 weeks after noise exposure, which in turn increases inflammatory cell infiltration [8,11] .…”
Section: Discussionmentioning
confidence: 99%
“…An emphasis on the roles of the cytokines may enable us to understand changes in hearing in association with changes in cytokine levels. TNF-α accumulates proinflammatory cells in the cochlea [11] . It was experimentally shown that the inhibition of TNF-α and suppression of inflammatory cells reduced hearing loss [4] .…”
mentioning
confidence: 99%